Corporate and supply chain network governance of third party logistics service providers: Effects on buyers’ intention to continue the relationship - Salih Börteçine Avci (Management şi Marketing, 2017)
This study focuses on the impact of corporate governance, supply chain network governance and competencies such as sales and logistics competence on buyers’ intention to relationship continuity. A total number of 258 questionnaires were distributed to Turkish manufacturing firms, selected using cross-sectional sampling method from the Istanbul and Edirne Chamber of Commerce and Industry in Turkey. The data of survey was analysed using PLS-SEM model with WARP PLS 5.0 software. Our findings indicate that corporate governance and supply chain network governance seem to have a positive effect on sales competence and logistics competence, and together, they influence buyers’ intention to relationship continuity. In this respect, the outcomes of this study may provide valuable insights for the third-party logistics (3PL) literature in terms of buyers’ intention to relationship continuity.